Age, ageing and sustainable work: where thus the buck stops? - Ramos, S.; Winston Jerónimo (22nd International Sustainable Development Research Society Conference, 2016)
Ageing is a global trend and one of the greater challenges of the current societies, with strong consequences on general population and particularly on workforce composition. In fact, ageing issues were been stressed on the agenda of European policies over the last years, with the establishment of goals intended to increase the employment rate of 55-64 workers and also increase of the retirement age. Demographic changes have a great impact on the composition of workforce. According to the 5th European Working Conditions Survey workers aged 50 and over represent 25% of employees in EU, which places a new challenge for corporate social responsibility. The most common answer for ageing at work has been the encouragement of ageing workers to remain active and at the same time convince companies to retain these older workers. But this aim cannot be achieved without an adaptive change of working conditions, considering the health and needs of older workers, providing the access to lifelong learning and rethinking benefits, rewards, participation, recognition and careers. Are companies aware of demographic trends and their impacts? Do the companies perceive ageing as a “social concern” or a “management issue”? Are they prepared to face this challenge inside them? In this sense, the purpose of our studies, conducted in Portugal, is to provide a comprehensive approach on age management topic, based on literature review but also on empirical work developed with Human Resources managers, trying to understand how companies evaluate and manage ageing, in the context of corporate social responsibility. Our findings suggest that Human Resources managers are generally concerned with age but they usually see this as an external problem, being mainly a society issue. Age is not being taken as a real challenge for companies while economic recession and youth unemployment are shaping the labor market. While economic recession is transitory, ageing is a structural trend and cannot be answered without a long-term approach based on public policies gathered with management practices. The managers’ short-term vision is a barrier to a strategic development and undermines the sustainability of organizations.